The Effects of Semantic Mapping on Reading Comprehension (LSP International Journal, 2017)
The aim of this study is to examine the effectiveness of semantic mapping strategy on reading comprehension of lower secondary school learners. The research questions explored include: (1) Does semantic mapping strategy have an effect on reading comprehension? (2) What are the students’ perceptions towards semantic mapping strategy in reading comprehension? The participants of this study were ten form-two students. Test 1(Pre-test), Test 2 (Post-test) and an interview were conducted in this study. Test 1 was administered before students were exposed to the semantic mapping strategy. After two weeks of semantic mapping exposure, Test 2 was administered to examine the effectiveness and improvement of the learners’ reading comprehension. Using mean scores, results showed that learners performed better in Test 2 than in Test 1, indicating the effectiveness of employing semantic mapping strategy in reading comprehension. From the qualitative analysis of the interview data, the findings showed that students enjoyed and learned better when semantic mapping strategy was employed.